(untitled) (Journal of Pedagogical Inventions and Practices, 2026)
The interrelationship between reading and writing plays a significant role in second language acquisition. These two productive and receptive skills are closely connected and mutually supportive in the process of language learning. Reading provides learners with linguistic input such as vocabulary, grammatical structures, sentence patterns, and discourse organization, while writing enables them to practice, internalize, and reproduce these language elements meaningfully. This article explores the strong connection between reading and writing for second language learners, emphasizing how reading comprehension enhances writing proficiency and how writing activities improve reading awareness. The study highlights the importance of integrated instruction, where both skills are taught simultaneously to improve academic performance and communicative competence. Furthermore, the article discusses practical classroom strategies that can strengthen reading-writing connections and foster learner autonomy